2019
DOI: 10.1017/s1751731118003269
|View full text |Cite
|
Sign up to set email alerts
|

A rapid shift to high-grain diet results in dynamic changes in rumen epimural microbiome in sheep

Abstract: The rapid shift to high-grain (HG) diets in ruminants can affect the function of the rumen epithelium, but the dynamic changes in the composition of the epithelium-associated (epimural) bacterial community in sheep still needs further investigation. Twenty male lambs were randomly allocated to four groups (n = 5). Animals of the first group received hay diet and represented a control group (CON). Simultaneously, animals in the other three groups (HG groups) were rapidly shifted to an HG diet (60% concentrate)w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 34 publications
7
22
4
Order By: Relevance
“…The present study showed that the genes responsible for glycolysis/ gluconeogenesis, pentose phosphate pathway, glycerolipid metabolism, and biosynthesis of ansamycins were upregulated in high energy feeding which indicates an enhanced fermentation rate performed by the rumen microbiota, with a decrease in the general function prediction only, arginine and proline metabolism, drug metabolism‐other enzymes, riboflavin metabolism, amino acid metabolism, novobiocin biosynthesis, and glutamatergic synapse‐related genes. These results are inconsistent with that of previous research (Seddik et al., 2018). The current study implied that feeding a high energy diet by using corn as the main energy source and decreasing the roughage percentage alters the ruminal microbial composition and the inferred microbial functions.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The present study showed that the genes responsible for glycolysis/ gluconeogenesis, pentose phosphate pathway, glycerolipid metabolism, and biosynthesis of ansamycins were upregulated in high energy feeding which indicates an enhanced fermentation rate performed by the rumen microbiota, with a decrease in the general function prediction only, arginine and proline metabolism, drug metabolism‐other enzymes, riboflavin metabolism, amino acid metabolism, novobiocin biosynthesis, and glutamatergic synapse‐related genes. These results are inconsistent with that of previous research (Seddik et al., 2018). The current study implied that feeding a high energy diet by using corn as the main energy source and decreasing the roughage percentage alters the ruminal microbial composition and the inferred microbial functions.…”
Section: Resultscontrasting
confidence: 99%
“…The current study also identified the changes of the represented genera in the rumen between the different dietary ME levels. For instance, unidentified Ruminococcaceae comprised 5.23%–7.02% of the relative abundance, which was inconsistent with previous studies (Seddik et al., 2018; Wang, et al., 2017). Ruminococcaceae strains play a critical role in energy and lipid metabolism, and its relative abundance is negatively associated with vascular sclerosis (Menni et al., 2018).…”
Section: Resultscontrasting
confidence: 84%
“…Not surprisingly, after abruptly switching to an HG diet, the colonic niche underwent comprehensive modification that included increased dietary starch content, enhanced total VFA production, promoted lactate, and decreased pH. These results were also mirrored by our previous study in rumen, which described a hallmark of the significant increased concentrations of ruminal butyrate, valerate, lactate and total VFA in the HG groups compared to their levels in the CON group [ 26 ]. Additionally, the high-starch diet drove clearly distinguishable changes in colon microbial ecosystems, and the duration of the HG-diet regulated the divergence and convergence of diet-microbe fingerprints in this study.…”
Section: Discussionsupporting
confidence: 60%
“…In the results, the most abundant functional categories contained amino acid metabolism, carbohydrate metabolism, replication and repair, membrane transport and translation, which were proved to be fundamental for the growth and reproduction of bacteria (Seddik et al . 2019). The G diet was predicted to lower the pathway of membrane transport than other diets.…”
Section: Discussionmentioning
confidence: 99%